ANALISIS SOSIAL EKONOMI KEBERADAAN USAHA AYAM RAS PETELUR DI KACAMATAN MARITENGNGAE KABUPATEN SIDRAP - Alfatiha, Ainaya; Marhawati, Marhawati; Said, Muh Ihsan; Ampa, Andi Tenri (Jurnal Pendidikan Ekonomi (JURKAMI), 2025)
This study aims to determine the social and economic existence of layer chicken business in Maritenngae District, Sidrap Regency. This research uses data collection techniques in the form of observation, interview and documentation methods. The subjects in this study were business owners, employees, and the local community. Data analysis techniques in this study used data reduction, data presentation and conclusion drawing. The results of this study indicate that the existence of the layer chicken business has an important role in the local economy. Layer chicken business, with the knowledge and experience of the business owner, plays an important role in running the business well. This business also provides livelihoods for the local community. It has a complex role in social and economic aspects. However, there are some challenges that need to be overcome, namely related to waste management and unpleasant odors that can disturb the environment and surrounding communities. Therefore, a sustainable approach to production and marketing as well as education and knowledge on proper waste management processes can help strengthen and sustain the layer business. The conclusion of this analysis considers the importance of maintaining a balance between social and economic aspects in maintaining and developing the business.